2021
DOI: 10.1002/ente.202001108
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Biomass Torrefaction and Gasification based on Biomass Classification: A Review

Abstract: Trace element migration and structure evolution are related to biomass gasification performance, which varies to a certain extent during torrefaction. This substantial summary of the integrated process based on biomass classification has practical significance for the consumption and commercialization of a bio‐refinery. Herein, biomass is divided into two categories and an understanding of the relevant variations is presented during the integrated two processes according to the classification. The effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 148 publications
(244 reference statements)
0
6
0
1
Order By: Relevance
“…However, the high water content, low energy density, and high O/C ratio of biomass often make it impossible to use it in the CLG process directly . Torrefaction is an effective means to overcome the above problems. , Numerous studies have shown that biomass undergoes complex physical and chemical changes after torrefaction, complicating its impact on downstream processes . For example, some studies have shown that higher gasification efficiencies are obtained with torrefied biomasses because their properties are closer to those of coal. , In other studies, a decrease in CGE and reactivity has been observed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high water content, low energy density, and high O/C ratio of biomass often make it impossible to use it in the CLG process directly . Torrefaction is an effective means to overcome the above problems. , Numerous studies have shown that biomass undergoes complex physical and chemical changes after torrefaction, complicating its impact on downstream processes . For example, some studies have shown that higher gasification efficiencies are obtained with torrefied biomasses because their properties are closer to those of coal. , In other studies, a decrease in CGE and reactivity has been observed .…”
Section: Discussionmentioning
confidence: 99%
“…26,73 Numerous studies have shown that biomass undergoes complex physical and chemical changes after torrefaction, complicating its impact on downstream processes. 74 For example, some studies have shown that higher gasification efficiencies are obtained with torrefied biomasses because their properties are closer to those of coal. 75,76 In other studies, a decrease in CGE and reactivity has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Gasification, a thermochemical process that exposes biomass to high temperatures and little oxygen, can be used to turn biomass into gaseous compoundsc [29][30][31] .…”
Section: Gaseous Productsmentioning
confidence: 99%
“…As a result, secondary and tertiary tar content is also expected to decrease. In addition, enhanced char reactivity due to increased alkali and alkaline earth metals, and a significant reduction in soot formation, are reported during torrefied biomass gasification (Lu et al, 2021). The gasification behaviour of torrefied biomass has been extensively studied in the literature.…”
Section: Application Of Torrefied Product In Thermochemical-based Bio...mentioning
confidence: 99%